Enabling the development of a sustainability best practice library - Nazir, Amir (Cranfield University, 2009)
Global environmental problems, rising energy prices, lack of raw material availability, increasingly demanding legislation and costly environmental taxes are some of the reasons that drive company policy towards adopting sustainability concepts and practices. This MSc thesis project aimed to carry on the research of industrial sustainability best practices in order to have a detail documentation that will aid the development of digital library. This is to help companies like CEMEX and their stakeholders to increase their sustainability awareness and enabling them to embed best practices in their operational processes. The research lacked clear and coherent method for mapping best practices from the literature into the adopted sustainable development process without validation. Nevertheless recommendations included proposing a separate study for the implementation of the sustainable development process and a further pilot study into implementing a few key best practices within industry. Overall this study was successful in helping to identify and validate best practices that were most frequently mentioned by academics and to some extent reflected the existing state of affairs concerning sustainable development and the environment.
Keywords: industrial sustainability; raw material availability; digital library; CEMEX; mapping best practices; sustainable development process